The Association of Nocturnal Blood Pressure Patterns and Other Influencing Factors With Lacunes and Enlarged Perivascular Spaces in Hypertensive Patients - Gao, Yang; Deng, Weiping; Sun, Jialan; Yue, Dongqi; Zhang, Bei; Feng, Yulan; Han, Jun; Shen, Fanxia; Hu, Jin; Fu, Yi (Frontiers in Neurology, 2022)
Purpose Nocturnal blood pressure dipping patterns have been associated with an increased risk of Cerebral Small Vessel Disease (CSVD), which has not been well-studied. This study is aimed to explore the association of dipping patterns and other factors with lacunes and enlarged perivascular spaces (EPVS) in patients with hypertension. Methods We enrolled a total of 1,322 patients with essential hypertension in this study. Magnetic resonance imaging (MRI) scans and 24-h ambulatory blood pressure (BP) monitoring were completed. Nocturnal BP decline was calculated, and then dipping patterns were classified. Patients were classified into four groups according to the performance of lacunes and EPVS in the MRI scan for statistical analysis. Results (1) Nocturnal BP decline showed independent negative correlation with both lacunes and EPVS while mean systolic BP (mSBP) level showed an independent positive correlation with them (P < 0.05). (2) The frequency of reverse-dippers in the control group was significantly lower than that in other groups; the frequency of non-dippers in the lacunes group and EPVS group was significantly lower than that in the control group; the frequency of extreme-dippers in the EPVS group was significantly higher than that in the mixed (lacunes with EPVS) group (P < 0.05). Conclusions Both mSBP and dipping patterns might play an important role in developing lacunes and EPVS in patients with hypertension.